Secondary school students knowledge toward oral health: a cross- sectional study - Khamees Abdullah , Sajida; Yasser Jumaa , Zainalabideen (International Journal of Advanced Nursing Studies, 2024)
Background: Oral health is strongly tied to oral health behaviors and knowledge. It is critical to assess teenagers' oral health information, even if they have received education, with the goal of instilling good lifestyle patterns that will last a lifetime. Objective: Tzhe objective of the study is to identify level secondary school students knowledge toward oral health Methodology: A descriptive cross-sectional study of 384 secondary school students probability selected schools in AL-Qadisiya Governorate, Iraq during the period (October 12th 2023 to March 25th 2024). Data collection through a self-report questionnaire consisting of two Parts: Demographic Data Form (age ,gender ,class ,monthly income and residency ) and questionnaire consist 18 multiple-choice questions secondary school students toward oral care . Results: The study included 384 students who participated in study, most of the sample reported a poor level regarding oral health (51.04%), while less than a third (28.12%) reported an average level and the remaining percentage (20.83) of those who had knowledge about oral health,with a mean of score (1.32). Furthermore, a statistically significant association was revealed between level knowledge and gender (p = 0.045) and residency (p = 0.000). Conclusions: The researchers concluded that level of knowledge of secondery school students regarding oral health is unacceptable and below the required level. Recommendations: The study recommended that allocating professional cadres trained to spread awareness about oral health among school students and the need to involve parents in the health education process directed at school children.